Prevalence of gastrointestinal nematode parasites of dogs and associated risk factors in Gondar town, Northwest Ethiopia - Tsedalu Yirsa; Amare Bihone; Getenew Teshager; Yimer Muktar; Abebe Berihun (Heliyon)
Intestinal parasites commonly infect dogs and can potentially spread to humans globally. Regrettably, numerous dog owners do not give priority to managing their pets' health, often ignoring treatment unless the animal is already ill. Thus, a cross-sectional study was conducted from December 2022 to April 2023 in Gondar town to determine the prevalence of gastrointestinal nematode parasites in dogs and their associated risk factors. A total of 204 dogs stool samples were collected using purposive sampling techniques. Direct fecal smear and flotation techniques were also used to identify the parasite ova. Chi-square and logistic regression were used to analyze the occurrence of the parasite within the risk factors. The overall prevalence of gastrointestinal nematodes in dogs was 47 (23.03 %) from the total 204 dog stool samples. Among these, Ancylostoma (9.31 %) was the most gastrointestinal parasite observed followed by Toxocara, Strongyloidea, and Trichurius. The dog positivity in gastrointestinal nematode occurrence had a statically significant association between age, sex, body condition, and housing management (P-value ≤ 0.05). Female dogs were 4.5 times (COR: 4.55) and young dogs were 3.5 times (COR: 3.5) more likely exposed to these parasites than their respective male and adult dogs. Regarding body condition scores, poor were 6.5 times (COR: 6.55; 95 % CI: 0.06–0.56) and medium was 0.5 times (COR: 1.5; 95 % CI: 0.26–0.9 9) more exposed than their comparable good body conditions. Generally, this finding suggests potential public health hazards associated with low levels of nematode infections in dogs.